2021
DOI: 10.3390/cancers13061278
|View full text |Cite
|
Sign up to set email alerts
|

Doxorubicin-Loaded Gold Nanoarchitectures as a Therapeutic Strategy against Diffuse Intrinsic Pontine Glioma

Abstract: Diffuse Intrinsic Pontine Gliomas (DIPGs) are highly aggressive paediatric brain tumours. Currently, irradiation is the only standard treatment, but is palliative in nature and most patients die within 12 months of diagnosis. Novel therapeutic approaches are urgently needed for the treatment of this devastating disease. We have developed non-persistent gold nano-architectures (NAs) functionalised with human serum albumin (HSA) for the delivery of doxorubicin. Doxorubicin has been previously reported to be cyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 76 publications
0
4
0
Order By: Relevance
“…Similarly, a lysine-methotrexate conjugate showed enhanced brain delivery using the endogenous BBB lysine transport system in an in vitro and pre-clinical rodent study [ 22 ]. Rodent studies indicate that gold nanoparticles can serve as a vehicle for targeted hydrophobic drug delivery through the BBB [ 62 , 63 ]. This was demonstrated using doxorubicin loaded gold nanoparticles in pre-clinical studies [ 64 , 65 ].…”
Section: Pre-clinical and Current Treatmentsmentioning
confidence: 99%
“…Similarly, a lysine-methotrexate conjugate showed enhanced brain delivery using the endogenous BBB lysine transport system in an in vitro and pre-clinical rodent study [ 22 ]. Rodent studies indicate that gold nanoparticles can serve as a vehicle for targeted hydrophobic drug delivery through the BBB [ 62 , 63 ]. This was demonstrated using doxorubicin loaded gold nanoparticles in pre-clinical studies [ 64 , 65 ].…”
Section: Pre-clinical and Current Treatmentsmentioning
confidence: 99%
“…185 effects. 188 Cheng et al modified Au NPs with a transactivator of transcription (TAT) peptide (5 nm core size), in which DOX was linked to a pH-dependent reversible hydrazone. TAT-Au-DOX doubled the intracellular penetration of DOX in U87 GBM cells compared to unloaded DOX.…”
Section: Review Biomaterials Sciencementioning
confidence: 99%
“…However, although in vitro studies indicated a that significant enhancement in apoptotic markers cleaved Parp, cleaved caspase 3, and phosphorylated H2AX expression in the treated cells by NAs-HSA-DOX, treatment of a pediatric GBM xenograft mouse model did not demonstrate NAs-HSA-DOX antitumor effects. 188 Cheng et al modified Au NPs with a transactivator of transcription (TAT) peptide (5 nm core size), in which DOX was linked to a pH-dependent reversible hydrazone. TAT-Au-DOX doubled the intracellular penetration of DOX in U87 GBM cells compared to unloaded DOX.…”
Section: Biomaterials For Gbm Drug Deliverymentioning
confidence: 99%
“…Doxorubicin and doxorubicin-loaded NAs-HSA had a similar effect on DIPG neurospheres. Colony formation assays demonstrated greater potency of NAs-HSA-Dox on inhibiting colony formation compared to doxorubicin [ 78 ]. Shargh et al developed three nanodelivery systems of TMZ analogue (N3Propargyl) including an apoferritin (AFt) nanocage, a sulfobutyl ether β-cyclodextrin (SBE-β-CD) nanocomplex, and SBE-β-CD in nanoliposomes and tested on 2D-spheroids and 3D obtained from DIPG cell lines resistant to TMZ.…”
Section: Nanoparticles and Brain Cscs Compartmentmentioning
confidence: 99%